Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Pneumonia di Ruangan Paru Rsud Prof.H. Muhammad Yamin, SH Pariaman - Siti Nurhafizah; Hilma Yessi; Debby Silvia Dewi; Linda Marni (CV. ITTC INDONESIA, 2026)
Pneumonia is a lower respiratory tract infection characterized by cough, shortness of breath, and sputum accumulation. Globally (2024), lower respiratory tract infections caused 2.18 million deaths, the majority of which were caused by the bacterium Streptococcus pneumoniae infection. In Indonesia (2023), there were 56,600 deaths caused by lower respiratory infections (LRI), of which pneumonia among individuals aged ≥60 years accounted for 23,600 deaths. The number of pneumonia cases in West Sumatra in 2022 reached 5,591 cases, while in Pariaman in 2024 there were 947 cases. Meanwhile, at RSUD Prof. H. Muhammad Yamin SH Pariaman in 2025, pneumonia ranked ninth with 89 cases. The purpose of this case study was to provide nursing care for a patient diagnosed with pneumonia. The method used was a six-day case study conducted through interviews, observation, and physical examination from February 10–15, 2026. The results identified six nursing diagnoses: ineffective airway clearance, ineffective breathing pattern, activity intolerance, sleep pattern disturbance, knowledge deficit, and risk of infection. The interventions implemented included airway management, respiratory monitoring, energy management, sleep support, health education, and infection prevention. Evaluation on the fourth day showed that the knowledge deficit had been resolved; on the fifth day, the ineffective breathing pattern, activity intolerance, and sleep pattern disturbance were resolved; and on the sixth day, ineffective airway clearance and risk of infection were fully resolved. Patients are advised to adopt a healthy lifestyle by avoiding exposure to dust, cigarette smoke, and air pollution, as well as consuming a balanced nutritious diet consisting of high-protein foods, vegetables, and fruits, and adhering to prescribed treatment in order to support the healing process and prevent recurrence. Families are expected to play an active role in providing support, including reminding patients to take their medication, refrain from smoking, and helping to maintain a clean and healthy environment.